Development and evaluation of a sepsis simulation with undergraduate nursing students - Martinez, Kelly; Aronson, Barbara (Nurse Education Today, 2024)
Background In 2016, the Centers for Disease Control found that more than 1.5 million people develop sepsis each year and about 250,000 Americans die from it. Early identification and treatment of sepsis can decrease mortality and morbidity, yet studies have shown student nurses are not prepared to rescue deteriorating patients. Method The purpose of this pilot study was to create and test a response to rescue simulation for use with undergraduate nursing students. The simulation depicted a patient deteriorating from sepsis. The Martinez Sepsis Competency Evaluation Tool (MSCET) developed to rate student behaviors during the simulation. Promoting Excellence and Reflective Learning in Simulation (PEARLS) debriefing model was used post simulation. Results The overall content validity of the MSCET was 0.88. Each item that scored a I-CVI of 0.78 or less were revised. The total percentage of behaviors met was 68 %. The inter-rater reliability of the MSCET conciseness was 0.47 (X = 67.508, df = 48, p ≤ .05). Conclusion The results indicate the simulation based experience was effective in preparing students to care for patients with early signs of sepsis. Students were complimentary about the experience, and preliminary data on the MSCET psychometrics were positive. Limitations of the study and recommendations for further revision of the simulation were made.
Keywords: Debriefing; Deterioration; Instrument development; Observers; Patient deterioration; Recognizing; Responding; Sepsis; Simulation; Undergraduate nursing students; Video-recorded; dept.nur; peer-reviewed